Rates of Early Recovery Following Thumb Carpometacarpal Arthroplasty: Comparing Ligament Reconstruction and Tendon Interposition, Abductor Pollicis Longus Suspensionplasty, and Suture Button Suspensionplasty - Lin, Lawrence J.; Sobba, Walter; Jacobi, Sophia; Paksima, Nader; Yang, S. Steven (Journal of Wrist Surgery, 2024)
Several techniques have been previously described for the treatment of thumb carpometacarpal (CMC) arthritis, including trapeziectomy with ligament reconstruction and tendon interposition (LRTI), abductor pollicis longus suspensionplasty (APLS), or suture button suspensionplasty (SBS). It remains unclear whether a specific method produces faster recovery and more rapid return to function. The purpose of this study was to evaluate early clinical outcomes in patients undergoing thumb CMC arthroplasty stratified by method of treatment.This study was conducted using a registry of patients undergoing thumb CMC arthroplasty using LRTI, APLS, or SBS. Patients were grouped by technique for comparison. Patient-reported outcomes were measured using Patient-Reported Outcome Measurement Information System (PROMIS) Upper Extremity, Pain Interference, and Pain Intensity scores and compared across cohorts using analysis of variance. Regression analysis was used to determine factors associated with early clinical outcomes.Note that 150 out of 201 patients met inclusion criteria for this study. Univariate regression demonstrated no difference between technique and achievement of minimal clinically important difference (MCID) by 1 year or ∆PROMIS scores at 1 and 3 months postoperatively. Stepwise multivariate regression analysis also found that technique did not contribute significantly to postoperative outcomes. Increased baseline PROMIS Upper Extremity scores were associated with lower odds of achieving MCID (odds ratio 0.80, p < 0.001). Baseline PROMIS scores were also associated with ∆PROMIS scores at 1 and 3 months postoperatively.Patients undergoing thumb CMC arthroplasty via LRTI, APLS, or SBS can expect to experience similar improvements from baseline in the early postoperative period regardless of technique choice.
Keywords: thumb carpometacarpal arthritis; thumb carpometacarpal arthroplasty; ligament reconstruction and tendon interposition; abductor pollicis longus suspensionplasty; suture button suspensionplasty